Assessment of reinforced concrete slabs using in-situ load testing: A case study. (September 2019) - Saleem, M.A.; Abbas, S.; Nehdi, M.L.
Abstract: In-situ load testing allows for assessment of the adequacy of existing structures with insufficient design information or unknown internal material deterioration history. In this study, flat slabs of an existing reinforced concrete (RC) building were evaluated using in-situ load testing per the ACI-318 test procedure. The tested structure had five storeys, among which two were underground. The building was to reach twelve storeys, yet construction was halted for eight years, exposing the structure to environmental damage mechanisms. Construction of the additional seven floors atop the existing ones required detailed analysis of the current condition. Hence, two slab panels on each floor were selected for performing in-situ load testing. Sand bags and loose sand were used to apply an incremental load on eight selected panels. Deflection measurements at critical locations along with thorough visual inspection were conducted during the loading and unloading cycles. Moreover, cores were retrieved from selected panels to investigate the compressive strength of the in-place concrete. No serious damage was observed during the in-situ loading and unloading cycles. However, slab panels of the first floor exhibited excessive cracking and deflection upon load testing. Deflection acceptance criteria were satisfied for all tested RC slab panels, except those of the first floor. The in-situ experimental results were validated through finite element analysis. It was determined that the existing RC structure had adequate strength to accommodate the new construction. However, it was recommended to demolish and reconstruct the first-floor slab panels. Highlights: Simple in-situ slab load test with uniform load proved effective. Deflection measurements at critical locations detected defective slab panels. Slab panels of first floor exhibited excessive cracking and deflection. Deflection acceptance criteria were satisfied except for first floor. Experimental results were validated via finite element analysis.